Reference interval of serum uric acid among healthy children and adolescents in Nanjing, China, and influencing factors - Luting Peng; Wu Yan; Yanan Shi; Mengyao Cao; Qianqi Liu; Xiaonan Li (Annals of Medicine)
Background Reference interval for serum uric acid (SUA) in children is based on adult standards. This study aimed to determine the reference interval and influencing factors of SUA in healthy children and adolescents.Methods From August 2020 to August 2022, 7,742 healthy children and adolescents aged 3–15 years receiving physical examinations at the Children’s Health Care Department at Children’s Hospital of Nanjing Medical University were recruited. A reference interval of SUA among children and adolescents was determined and validated in a cohort of 2,968 children. Influencing factors of SUA levels were identified by linear regression analyses.Results Among 7,742 healthy children and adolescents with an average age of 8.2 ± 2.3 years, the average SUA level was 4.5 ± 0.98 mg/dl, and significantly higher in boys than girls. Age-specific increase in the SUA level started from the age of 8 years. A significantly higher SUA level was detected in boys than in girls among those older than 12 years. The reference interval of SUA among healthy children and adolescents in the age groups of 3–8 years, 9–10 years, 11 years was established as 2.8–6.1 mg/dl, 2.9–6.4 mg/dl, and 3.1–7.4 mg/dl, respectively. For those aged 12–15 years, the reference interval of SUA was 3.5–8.7 mg/dl in boys and 3.4–7.7 mg/dl in girls. Linear regression analysis indicated that SUA was positively correlated with the body fat percentage, skeletal muscle mass, and alanine aminotransferase, while negatively correlated with estimated glomerular filtration rate.Conclusion The distributions of SUA levels are age and gender-specific among healthy children and adolescents in Nanjing, China. The established distinct reference interval of SUA and diagnostic criteria for hyperuricemia in this population may assist in the clinical management of related diseases.